ADOLESCENT’S RESILIENCE IN INDONESIA: WHAT CAN WE LEARN FROM PANDEMIC OF COVID-19? - Alfiasari, Alfiasari; Salsabila, Syifa; Khairunisa, Yasmin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Resilience plays a crucial role in adolescent development, particularly during crises such as the Covid-19 pandemic, which disrupted education, family dynamics, and social interactions. This study aimed to investigate the impact of social support from friends and teachers, as well as mother-child communication, on adolescent resilience during the pandemic. An explanatory design with a quantitative approach was employed, with data collected online from 202 adolescents across Java Island through questionnaires distributed via social media platforms. The study sample consisted of junior and senior high school students participating in distance learning during the pandemic. The findings indicated that 67.3% of adolescents showed moderate resilience, while 6.9% displayed high resilience. Correlation analysis revealed significant relationships between social support from friends (r = 0.146), social support from teachers (r = 0.270), and mother-child communication (r = 0.206) with adolescent resilience. Regression analysis showed that social support from teachers had the most significant positive effect on resilience, explaining 8% of the variance in adolescent resilience. These findings suggest that enhancing teacher support and improving family communication are key strategies to foster adolescent resilience during crises such as the Covid-19 pandemic.